Prevalencia de riesgo de sepsis en el servicio de neonatología del Hospital General José María Velazco Ibarra De Tena. Año 2013 – 2014 - Jessica Alexandra Bueno Maceira (2015)
This study focused on investigating the prevalence and causes sepsis in neonate’s neonatology service of the General Hospital José Maria Velasco Ibarra de Tena. The purpose of this study is to propose nursing actions aimed at reducing risks and promoting the cause to the attention of the quality that guarantees health of newborns. Research are applied to 60 mothers of babies born in the General Hospital José Maria Velasco Ibarra, for 3 months of September to November 2013. The results obtained were that of 175 infants admitted to neonatal ward with different pathologies, 60 infants are at risk of neonatal sepsis, with 34%, it is concluded that mothers have little knowledge about risk of neonatal sepsis, because most mothers are adolescents, indigenous ethnic group, with a minimum number of antenatal. They have not been trained on the subject, in conclusion the high risk of neonatal sepsis is given by the lack of maturity, knowledge of mothers of newborns. The research design is not experimental, not transverse, descriptive, field collection techniques bibliographic data, fixed the survey and observation with their respective instruments are applied, the proposed nursing intervention is planned in Based on the results obtained. As proposed specifying the researcher developed a manual that is risk of sepsis and focusing what causes it, the importance of prenatal care and nursing care Keywords: Risk, sepsis, prevalence, neonates